Powrót „Dziadów”, czyli dwa teatry - Kopiciński, Jacek (Załącznik Kulturoznawczy, 2015)
The essay of Jacek Kopciński is dedicated to new realisations of Adam Mickiewicz’s Dziady (Forefathers’ Eve) in contemporary Polish theatre.The author juxtaposes performances of two leading avant-garde directorsof younger generation: Michał Zadara and Paweł Passini, and analyses theinterviews of both artists. The purpose of the essay is to reconstruct theirartistic consciousness. This reconstruction leads to illustrate two interpretivestrategies that correspond with different directions of development of Polishcontemporary theatre. Zadara stages the entire text of the drama, but distortsits meaning to build a critical distance to romantic myths. Passini, however,made an adaptation of the drama, followed its metaphysical meaning andexposed it as a rite consistent with romantic idea. The author of the articleputs Zadara’s performance in the current of critical theatre, while Passini’sintepretation is treated as an alternative proposal called imagined communitytheatre. The context for this discussion is the jubilee of the 250 anniversaryof the National Theatre and the public theatre in Poland.